Buyer–seller interaction in experimental spatial markets - Camacho-Cuena, Eva; Garcı́a-Gallego, Aurora; Georgantzı́s, Nikolaos; Sabater-Grande, Gerardo (Regional science and urban economics, 2005)
We report results from experimental spatial markets with endogenous buyer location on a discrete version of Hotelling's linear city. Buyer locations favor more often the hypothesis of transportation cost minimization than that of strategic location aimed at increasing price competition between sellers. However, the latter of the two hypotheses receives systematic support too. Differentiation by seller-subjects is substantially less than the theory would predict for the specific framework used. Our results suggest that location strategies adopted by subjects can be seen as a rational process favoring conservative product design and spatial agglomeration of economic activities.